Factorization of motion polynomials. (May 2019) - Li, Zijia; Schicho, Josef; Schröcker, Hans-Peter
Abstract: In this paper, we consider the factorizations of monic, bounded motion polynomials. We prove existence of factorizations, possibly after multiplication with a real polynomial Q, and provide an algorithm for computing Q and corresponding factorizations. The algorithm gives a much lower bound on the degree of the polynomial factor than the mere existence theorem.